IFN‐γ stimulates CpG‐induced IL‐10 production in B cells via p38 and JNK signalling pathways. Issue 9 (1st August 2018) - Imbrechts, Maya; De Samblancx, Karen; Fierens, Karlien; Brisse, Ellen; Vandenhaute, Jessica; Mitera, Tania; Libert, Claude; Smets, Ide; Goris, An; Wouters, Carine; Matthys, Patrick
Abstract: The production of IL‐10, a potent immunosuppressive cytokine, must be strictly regulated to ensure a balanced immune response. IFN‐γ, a key cytokine in multiple immune processes and pathologies, is known as an inhibitor of IL‐10 production by monocytes and macrophages, but also has some regulatory functions. In the present study, we explored the role of IFN‐γ on Toll‐like receptor (TLR)‐induced IL‐10 production in murine peritoneal and spleen cells and in human peripheral blood mononuclear cells. IFN‐γ inhibited IL‐10 production induced by TLR2, TLR3, TLR4 and TLR7/8 agonists, but stimulated IL‐10 production when cells were triggered with CpG oligodeoxynucleotides, a specific TLR9 agonist. The stimulatory effect of IFN‐γ on TLR9‐induced IL‐10 was restricted to B cells. In line with the increased IL‐10, B cells stimulated with CpG and IFN‐γ profoundly inhibited CD4 T cell proliferation. Further research into the mechanisms involved, revealed that the mitogen‐activated protein kinases p38 and JNK are essential players in this stimulatory effect, and that the phosphatase MKP1 – an inhibitor of p38 and JNK activity – is downregulated after combined stimulation with IFN‐γ and CpG. Our data may represent a novel immunoregulatory role of IFN‐γ in B cells after triggering of TLR9, by stimulating IL‐10 production. Abstract : While IFN‐γ inhibits TLR‐induced IL‐10 in macrophages (left), it stimulates CpG‐induced IL‐10 production in B cells by preventing the activity of MKP1, an inhibitor of p38 and JNK protein kinases. Promoting TLR9‐induced IL‐10 production in B cells may represent a novel immunoregulatory role of IFN‐γ.